2020
DOI: 10.1097/txd.0000000000001086
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Hepatocellular Carcinoma Surveillance Practices Following Liver Transplantation

Abstract: Background. Recurrence of hepatocellular carcinoma (HCC) is an important predictor of survival after liver transplantation (LT). Recent studies show that early diagnosis, aggressive treatment, and surveillance may improve outcomes after HCC recurrence. We sought to determine the current practices and policies regarding surveillance for HCC recurrence after LT. Methods. We conducted a web-based national survey of adult liver transplant centers in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…These results strongly support the need for personalized post-LT HCC screening procedures based on individual risk of HCC recurrence. There is currently no consensus on post-LT surveillance strategies and a recent study from the United States showed surveillance strategies remain highly heterogeneous across US centers (35). Also, some centers do not screen for HCC recurrence due to concerns on cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly support the need for personalized post-LT HCC screening procedures based on individual risk of HCC recurrence. There is currently no consensus on post-LT surveillance strategies and a recent study from the United States showed surveillance strategies remain highly heterogeneous across US centers (35). Also, some centers do not screen for HCC recurrence due to concerns on cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Late recurrences happen at between 2 and 5 years. A recurrence after 5 years is rare [ 18 ]. They concern the liver (from 27% to 45%), but more frequently they appear in other locations (around 60%), mainly in lungs and bones, and less often in the adrenal glands, peritoneum, and lymph nodes [ 7 , 18 , 91 , 121 123 ].…”
Section: Surveillance Treatment Of Recurrencementioning
confidence: 99%
“…A meta-analysis of 2003 HCC patients who underwent LT indicated that MVI was related to 2.3-fold decrease of 5-year OS rate compared with those without MVI ( 6 ). Therefore, MVI was the most common factor used in risk stratification and surveillance for HCC recurrence after LT ( 65 ). Bhatti et al.…”
Section: And Surgical Outcomesmentioning
confidence: 99%